The Impacts of Free Quality Education on HouseHolds in Makeni City - Samuel Karim; Exton Mohamed Zoker; Mamawoh Karimu; Hasanatu Hawantu Hassan (CV. Edutechnium Indonesia, 2023)
This work was carried out to examine the impact of the free quality education on households in Makeni City. Education is believed to be a key factor for sustainable social and economic development, thus the reason it is one of the sustainable developments global goals. For several years, some countries have been funding (in full or in part) the education of their citizens to reduce the economic burden of low-income families. This initiative has had tremendous impacts on the learners, educators, parents, and community in general. This study therefore was set determines the impacts of the free quality education on households in Makeni city, in the northern province of Sierra Leone. The impacts of the free quality education on households were measured by the opinions of teachers, parents and the pupils in the city. It was conducted out of the assumption that, the better the quality of free education, the higher the chances for livelihood sustainability. The specific objectives are to determine: the impacts of free quality education on teacher’s performance, to determine the impacts of free quality education on students learning outcome, and also to determine the perceptions of parents about the free quality education. Descriptive research design was used to conduct the study, with a sample of 61 teachers, 100 parents, and 100 pupils were selected purposively in the case of the teachers, and randomly in the case of the parents and pupils across the board in Makeni city. Data were collected from both primary and secondary source, with questionnaire as the main instrument for the collection of primary data. After the collection of data, responses were summarized in a matrix, after which the data was presented in tables and charts, followed by an interpretation of what each table and chart represents. The major findings were that the free quality education was a free tuition with no extra charges and supply of exercise books and textbooks. It however lacked in terms of active school-feeding and free school buses. In addition, it affected teachers’ performance in terms of competency in teaching their subjects, assessing students and in dealing with their colleagues. Some of the recommendations which were made were that, there should be frequent refresher trainings, active school feeding in all schools, mass sensitization and effective monitoring in schools in Makeni City.